The Effectiveness of Speech-Ace Website on Students’ Pronunciation - Mutiara, Anggytha; Wakhda, Salma Chusna; Alfidariyani, Ismi Maryam; Indriani, Lilia (English Education:Journal of English Teaching and Research, 2024)
Effective communication is the core of an EFL program. Therefore, having good pronunciation is crucial to achieve effective communication and to avoid misunderstanding. Speech-Ace is a tool that helps to enhance pronunciation in the form of a website. This study aims to discover the effectiveness of Speech-Ace on English Education Department student's pronunciation. Qualitative approach with case study method was used in this study, the data were gathered through pronunciation tests and interviews. The result showed that there was improvement in student's pronunciation after the implementation of Speech-Ace website. Students were helped by the feedback from the Speech-Ace website in enhancing their pronunciation skills. However, the study's generalizability is limited by the small sample size of 30 students. Further research with a larger and more representative population could strengthen the validity of the findings.